Avaliação dos resultados clínicos e humanísticos de um plano de atenção farmacêutica em pacientes asmáticos - Dantas, Solange Cecilia Cavalcante (2007)
The high prevalence of poorly controlled asthma and the associated high morbimortality have been shown to be related mainly to under-diagnosis and inadequate treatment of this condition. This present significant cost adding further burden on the healthcare budget The consequences of poorly controlled asthma are repeated clinic visits repeated emergency room admissions and repeated hospital admissions In extreme but numerous occasions asthma attacks resulting from poor management lead to deaths Therefore it had been stated that a key component of many asthma management guidelines is the recommendation for patient education and regular medical review These (patient education and regular medication/medical reviews) are primary areas for the pharmacist to make an impact Objective To describe and to analyze the influence of a Pharmaceutical Care (PC) service in the clinical and humanistic outcomes through the pharmacotherapeutic follow-up (PF) of a group of asthmatic patients attending an ambulatory care facility by hospital referral in the State of the Ceará Methods Thirty patients participated of this longitudinal prospective and descriptive study in the period from August 2006 to May 2007 Instruments used to collect information from patients were an asthma-specific quality of life questionnaire (The Brazilian version of the Asthma Quality of Life Questionnaire AQLQ) daily records of symptoms of the asthma and a questionnaire to assess satisfaction with Pharmaceutical Care services The PF and the classification of drug related problems (DPR) followed Cipolle et al criteria (2004) and adopted a systematic PWDT (Pharmacist’s Work up of Drug Therapy) approach in identifying and resolving DPR Results The majority of patients were females (80%) 10% completed primary school level only mean age was 46 ± x 11 9 30% were on married social pension and with income of two minimum salaries Patients used an average of two inhaled medications (corticosteroids and bronchodilator) /day and more than 50% of patients did not use their inhaler medication devices correctly Sixty four DPR were identified, of which 31 25% were related to poor compliance with drug therapy After the provision of Pharmaceutical Care and through following a PWDT strategy 66 6% of the patients did not report nocturnal symptoms of asthma and did not have to use short-acting bronchodilator for asthma symptoms By the conclusion of the study a significant improvement (p< 0 05) was observed in the four domains of the AQLQ In the questionnaire assessing satisfaction with the Pharmaceutical Care services a superior index of 95% was observed in all its domains Conclusion The improvement seen in all aspect of the outcomes measured including clinical and humanistic outcomes after the provision of PC has provided evidence for the role of the pharmacist in asthma management using a structured approach to educate the patient about the pharmacotherapy regimen address compliance issues and making drug therapy interventions that lead to rationalizing therapy and minimizing DPR